A degranulation assay using Vγ9Vδ2 T cells for the rapid diagnosis of familial hemophagocytic syndromes - Jorisch-Mühlebach, Olivia; Pitts, Dina; Tinner, Raphaela; Teh, Hong Ying; Roelli, Conrad; Prader, Seraina; Vavassori, Stefano; Pachlopnik Schmid, Jana (Frontiers in Immunology, 2024)
Introduction Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening immune disorder characterized by uncontrolled lymphocyte and macrophage activation and a subsequent cytokine storm. The timely initiation of immunosuppressive treatment is crucial for survival. Methods Here, we harnessed Vγ9Vδ2 T cell degranulation to develop a novel functional assay for the diagnosis of HLH. We compared the novel assay with the conventional natural killer (NK) cell stimulation method in terms of efficiency, specificity, and reliability. Our analysis involved 213 samples from 182 individuals, including 23 samples from 12 patients with degranulation deficiency (10 individuals with UNC13D deficiency, 1 with STXBP2 deficiency, and 1 with RAB27A deficiency). Results While both tests exhibited 100% sensitivity, the Vγ9Vδ2 T cell degranulation assay showed a superior specificity of 86.2% (n=70) compared to the NK cell degranulation assay, which achieved 78.9% specificity (n=213). The Vγ9Vδ2 T cell degranulation assay offered simpler technical requirements and reduced labor intensity, leading to decreased susceptibility to errors with faster processing times. Discussion This efficiency stemmed from the sole requirement of dissolving (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP) powder, contrasting with the intricate maintenance of K562 cells necessary for the NK cell degranulation assay. With its diminished susceptibility to errors, we anticipate that the assay will require fewer repetitions of analysis, rendering it particularly well-suited for testing infants. Conclusion The Vγ9Vδ2 T cell degranulation assay is a user-friendly, efficient diagnostic tool for HLH. It offers greater specificity, reliability, and practicality than established methods. We believe that our present findings will facilitate the prompt, accurate diagnosis of HLH and thus enable rapid treatment and better patient outcomes.